Analisis Pengelolaan Dana Desa dalam Upaya Meningkatkan Pembangunan Desa di Desa Lobodei Kecamatan Sabu Timur - Gordon Wiliam Angrilon Rihi; Aldarine Molidya; Cicilia A. Tungga (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the management of village funds in an effort to improve village development in Lobodei Village, East Sabu District. The research method used was qualitative descriptive with observational data collection techniques, structured interviews with 11 informants, and documentation studies. Data analysis is assisted by the Nvivo application version 15. The results of the study show that in general, the management of village funds in Lobodei Village has referred to Permendagri Number 20 of 2018, but the implementation has not been optimal. The planning stage is not appropriate because the determination of the APBDesa is often late past the deadline. The implementation stage is also considered not optimal due to the existence of the Remaining Budget Calculation (SiLPA). The administration and reporting stages are considered to need improvement because financial administration reports are often late and not periodic, while the accountability stage is considered good. The main supporting factors are accountability, community participation, and transparency. Meanwhile, the main inhibiting factors include the competence and quality of human resources of village apparatus, as well as the use of technology such as the Siskeudes application which is not optimal due to internet network constraints.